Best original research presented at the 25th European Congress on Gynaecological Oncology: best of ESGO 2024 - Kacperczyk-Bartnik, Joanna; El Hajj, Houssein; Bizzarri, Nicolò; Bilir, Esra; Zwimpfer, Tibor Andrea; Strojna, Aleksandra Natalia; Gasimli, Khayal; Angeles, Martina Aida; Ghirardi, Valentina; Erfani, Hadi; Nikolova, Tanja; Theofanakis, Charalampos; et al. (International journal of gynecological cancer, 2024)
The 'Best of ESGO 2024' article includes a selection of the most highly rated original research presented during the 25th Annual Congress of the European Society of Gynaecologic Oncology (ESGO), held in Barcelona, Spain, March 7-10, 2024. Of 1218 asbtracts submitted, 35 studies presented during the best oral sessions, mini oral sessions, best three minute presentations session, and young investigator session were selected by the ESGO abstract committee and the authors of the European Network of Young Gynae Oncologists (ENYGO). There was a strong focus on the surgical treatment of early stage cervical cancer and the management of advanced or recurrent gynecological cancers using induction therapy, immunotherapy, and maintenance therapy. With this work, ENYGO and ESGO aim to focus the attention of clinicians, scientists, patients, and all stakeholders interested in gynecologic oncology on research advances in the field.